A new approach for determining GND and SSD densities based on indentation size effect: An application to additive-manufactured Hastelloy X. (10th January 2022) - Cui, Luqing; Yu, Cheng-Han; Jiang, Shuang; Sun, Xiaoyu; Peng, Ru Lin; Lundgren, Jan-Erik; Moverare, Johan
Highlights: A new approach to determine GND and SSD densities for FCC metals was established. The new approach was based on indentation size effect and classical strengthening theories. Results of new approach were verified by conventional Hough-based EBSD and XRD CMWP methods. Due to low SFE of L-PBF Hastelloy X, edge-GNDs contribute greatly the increment of strengthening. Dislocation distribution shows grain orientation-dependent: low in large <101> grains, high in fine <001> grains. This method may construct a firm basis for future quantitative work on BCC and HCP metals. Abstract: Dislocation plays a crucial role in controlling the strength and plasticity of bulk materials. However, determining the densities of geometrically necessary dislocations (GNDs) and statistically stored dislocations (SSDs) is one of the classical problems in material research for several decades. Here, we proposed a new approach based on indentation size effect (ISE) and strengthening theories. This approach was performed on a laser powder bed fused (L-PBF) Hastelloy X (HX), and the results were verified by the Hough-based EBSD and modified Williamson–Hall (m-WH) methods. Furthermore, to better understand the new approach and essential mechanisms, an in-depth investigation of the microstructure was conducted. The distribution of dislocations shows a clear grain orientation-dependent: low density in large <101> preferentially orientated grains while high density in fine <001> orientated grains. The increment of strengthening in L-PBF HX is attributed to a huge amount of edge-GNDs. Planar slip is the main operative deformation mechanism during indentation tests, and the slip step patterns depend mostly on grain orientations and stacking fault energy. This study provides quantitative results of GND and SSD density for L-PBF HX, which constructs a firm basis for future quantitative work on other metals with different crystal structures. Graphical abstract: Image, graphical abstract